(untitled) (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article examines the essence of problem-based learning technology within the methodology of teaching Russian as a foreign language. Problem-based learning is conceptualized as a didactic system grounded in the creation of educational problem situations that stimulate cognitive activity, the independent search for solutions, and the development of students’ speech-and-thought processes. The analysis establishes that this technology fosters the development of linguistic inference skills, the formation of abilities for independently constructing utterances, and a transition from the reproductive assimilation of linguistic material to its functional application in communication